Microstructural characterization of squeeze-cast Al-8Fe-1.4V-8Si - Arhami, M.; Sarioglu, F.; Kalkanli, A.; Hashemipour, M. (Elsevier Science Sa, 2008)
This paper investigates the effect of vanadium on the composition and morphology of intermetallics formed during the squeeze casting of Mg-modified Al-8Fe-1.4V-8Si alloy in both monolithic form and as-reinforccd with 7.58,10.52 and 15.68 wt.% SiC particles (SiC(p)). Iron intermetallics of alpha-Al(7)(Fe,V)(3)Si and beta-Al(18)Fe(11)Si phases were predominantly observed in the alloy and composite. SEM studies and the EDX analyses revealed that refinement of Fe-intermetallics and modification of beta-phases to less deleterious morphologies of alpha-phases has been achieved by vanadium addition of 1.4%. Also, heat treatment enhances V diffusion and SiC particles act as nucleation sites for the formation of finer alpha-intermetallics. Fractographs exhibited cracking of long P-phases and partial decohesion of SiC(p) from the matrix. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Al-Fe-V-Si alloy; squeeze casting; intermetallic phases; vanadium; SiC particles